2008
DOI: 10.1179/joc.2008.20.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Azithromycin 1 g Once Daily for 3 Days in the Treatment of Community-Acquired Pneumonia: an Open-Label Randomised Comparison with Amoxicillin-Clavulanate 875/125 mg Twice Daily for 7 Days

Abstract: This randomised, open-label, non-inferiority study was designed to demonstrate that a 3-day course of oral azithromycin 1 g once daily was at least as effective as a standard 7-day course of oral amoxicillin-clavulanate 875/125 mg twice daily in the treatment of outpatients with community-acquired pneumonia (Fine class I and II). In total, 267 patients with clinically and radiologically confirmed community-acquired pneumonia were randomly assigned to receive either the azithromycin (n=136) or the amoxicillin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 10 publications
0
24
0
3
Order By: Relevance
“…The cure rate for erm B strains was estimated to be near-zero by this method, but was also set to 5% to avoid introducing an ab initio difference between the two strains. The cure rate was estimated to be 88% for the antibiotic-sensitive strain, by extrapolating estimated treatment efficacies of around 93% from studies that used higher doses of azithromycin, but in populations that presumably harbored resistance [30], [31].…”
Section: Methodsmentioning
confidence: 99%
“…The cure rate for erm B strains was estimated to be near-zero by this method, but was also set to 5% to avoid introducing an ab initio difference between the two strains. The cure rate was estimated to be 88% for the antibiotic-sensitive strain, by extrapolating estimated treatment efficacies of around 93% from studies that used higher doses of azithromycin, but in populations that presumably harbored resistance [30], [31].…”
Section: Methodsmentioning
confidence: 99%
“…[17161] Various studies have shown results favoring different groups of antibiotics [Table 7]. [165–169171–174178–184] The evidence does not support the choice of any particular antibiotic since individual study results do not reveal significant differences in efficacy between various antibiotics and antibiotic groups. [175] The commonly used antibiotics are either ÎČ-lactams or macrolides.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…The search for RCTs yielded 5,495 titles. After applying inclusion and exclusion criteria, 43 RCTs were included in the final analysis (Figure ): two trials of CAP‐C; three of mixed CAP‐C and CAP‐H, 20 of CAP‐H, two of mixed CAP‐H and HCAP, three of HCAP, six of HAP, five of VAP, and two of HAP and VAP . Two CAP‐H trials targeted a priori an elderly population …”
Section: Resultsmentioning
confidence: 99%